Laser ablation behavior of C/SiC composites subjected to transverse hypersonic airflow. (1st May 2021) - Wang, Zhe; Wang, Jiangtao; Song, Hongwei; Yuan, Wu; Liu, Yuwen; Ma, Te; Huang, Chenguang
Highlights: Transverse hypersonic airflow multiplied the laser ablation mass loss and changed the ablation mechanisms of C/SiC composites. Tattered microstructure instead of needle-like were found for laser ablated carbon fibers in the hypersonic airflow condition. Ablation models revealed that the accelerated ablation rates are mainly attributed to the strong mechanical erosion effect. Abstract: Laser ablation behaviors of C/SiC composites were examined in a hypersonic wind tunnel. Parallel laser ablation tests under static air were also conducted, and the ablation behaviors of these two conditions were compared. Mass ablation rates were augmented by 4–9 times when subjected to the hypersonic airflow. Ablation morphologies were significantly different in the micro and macro scales, and the needle-like microstructure of carbon fibers under static air turned to be rough and tattered under the hypersonic airflow. The accelerated ablation rate and the peculiar ablation micro-morphologies were mainly attributed to the strong mechanical erosion induced by hypersonic airflow.